Creativity-Based Music Education for Kindergarten: Integrating Musical Literacy and Emotional Intelligence at PPPK Petra - Karthika, Guido Denta Christian; Sekti, Retnayu Prasetyanti; Juwariyah, Anik (Jurnal Paedagogy, 2026)
This study aims to analyze the creative application of music education through the integration of musical literacy—encompassing media use and teaching strategies—into activities that foster emotional intelligence among kindergarten children at PPPK Petra. The research employed a descriptive qualitative approach. Data were collected in the form of verbal data and visual documentation through direct classroom observations of children during music learning activities, interviews with music teachers and homeroom teachers, and interviews with parents. The data were analyzed through three stages: data reduction, data display, and conclusion drawing and verification. The findings indicate that music education integrating two paradigms—education about music and education through music—can create interactive and meaningful learning experiences. Children not only acquire a basic understanding of rhythm, pitch, and musical symbols, but also apply this understanding in activities that foster self-motivation, empathy, and collaborative skills. These findings confirm that the integration of musical literacy with emotional development is effective, as children learn through direct, contextual, and collaborative experiences. In conclusion, creative and comprehensive music education contributes not only to students’ cognitive development but also to the formation of positive behaviors and character, serving as essential preparation for their future lives.